(untitled) (Educational Dimension, 2019)
This paper introduces Educational Dimension, a new Diamond Open Access peer-reviewed journal that publishes research on education, learning and training, and applications of theories and philosophies used in the sciences of learning and adjacent sciences. The paper provides information about the journal’s history, scope, editorial board, and publication ethics. The paper also invites scholars from all over the world to submit their original research papers, systematic reviews and meta-analyses to the journal.